Grammar and Social Organization: Yes/No Interrogatives and the Structure of Responding - Raymond, Geoffrey (American Sociological Review, 2003)
Connections between grammar and social organization are examined via one of the most pervasive practices of speaking used in talk-in-interaction: yes/no type interrogatives and the turns speakers build in response to them. This investigation is composed of two parts. The first analyzes a basic organization set in motion by yes/no type interrogatives, describing a preference for “type-conforming” responses and its consequences. The second considers how this basic organization is shaped and simplified to accomplish institutionally specific goals in survey research, medical encounters, and courtroom cross-examinations, and what such manipulations reveal about these institutions. Together these findings deepen our understanding of how language is adapted to—and for—interaction, while providing analytic resources for a broad range of sociologists, whether they are engaged in the direct observation of human behavior, developing sociological theories of language, analyzing institutions and social organizations, or interested in the practical consequences of questioning in the myriad institutions that make use of this form.